Do the sticky floor and glass ceiling phenomena persist in the Indonesian labour force after the pandemic? - Ruslan, Kadir; Sukma, Weni Lidya (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2025)
Our study aims to examine the evolution of gender wage gaps and their decomposition by employment status in Indonesia during the pre-pandemic, pandemic, and post-pandemic periods, using SAKERNAS data from 2018 to 2023. The OLS and RIF-OLS regression estimations reveal that gender wage gaps remained substantial throughout these periods. On average, female employees earned about 30 percent less than their male counterparts, which decreased to 23 percent after controlling for other wage-related characteristics. Notably, the gap is particularly pronounced among underemployed and low-paid workers, where female employees earn approximately 40 percent to 50 percent less than their male counterparts. Decomposition results using Blinder-Oaxaca and RIF-Oaxaca methods, both at the mean and across the wage distribution, pointed out that most of the gap is due to unexplained factors, confirming the persistence of the sticky floor and glass ceiling phenomena. This suggests ongoing negative discrimination against female employees in the Indonesian labor market. Among observable characteristics, working experience, tenure, and working hours significantly contributed to the wage gap, with women generally lagging behind men in these areas. However, women’s higher educational attainment, greater participation in the formal sector, access to training, and prevalence in white-collar jobs significantly helped reduce the wage gaps.